Conjunctival Scarring, Corneal Pannus, and Herbert's Pits in Adolescent Children in Trachoma-endemic Populations of the Solomon Islands and Vanuatu. (10th August 2020) - Butcher, Robert; Tagabasoe, Junely; Manemaka, Joseph; Bong, Annie; Garae, Mackline; Daniel, Lui; Roberts, Chrissy; Handley, Becca L; Hu, Victor H; Harding-Esch, Emma M; Bakhtiari, Ana; Willis, Rebecca; et al.
Abstract: Background: In the Solomon Islands and Vanuatu, the sign trachomatous inflammation—follicular (TF) is common, but ocular infection with Chlamydia trachomatis is not. It is therefore debatable whether azithromycin mass drug administration (MDA), the recommended antibiotic treatment strategy for trachoma's elimination as a public health problem, is necessary in this setting. We set out to estimate what proportion of adolescents were at risk of progression of trachomatous scarring. Methods: A cross-sectional survey was undertaken of all children aged 10–14 years resident in communities identified as high-TF clusters during previous population-based mapping. Graders examined children for clinical evidence of trachomatous scarring, pannus, and Herbert's pits (HPs) or limbal follicles in both eyes. A dried blood spot was collected from each child and tested for antibodies to C. trachomatis . Results: A total of 492 children in 24 villages of the Solomon Islands and Vanuatu were examined. In total, 35/492 (7%) of children had limbal signs (pannus and/or HPs) plus any conjunctival scarring. And 9/492 (2%) had limbal signs and moderate or severe conjunctival scarring; 22% of children were anti-Pgp3 seropositive. Conclusions: Few adolescents here are at risk of future complications from trachoma, supporting the conclusion that further antibiotic MDA is not currently required for trachoma elimination purposes in these settings. Abstract : In Solomon Islands and Vanuatu communities in which active trachoma prevalence in children was previously high, prevalence of Herbert's pits or pannus plus conjunctival scarring in 10–14-year-olds is low, suggesting risk of future trachomatous blindness here is also low.